Antagonistic interactions between heterotrophic bacteria as a potential regulator of community structure of hypersaline microbial mats. Issue 1 (6th August 2012) - Long, Richard A.; Eveillard, Damien; Franco, Shelli L.M.; Reeves, Eric; Pinckney, James L.
Abstract Microbial mats are laminae of self‐sustaining microbial communities with a high level of competition for resources. We tested the hypothesis that chemically mediated antagonism is a potential mechanism for structuring the bacterial community. In the co‐culturing assay, 57% of the isolates expressed antagonistic behavior toward one or more isolates and 5% of the isolates inhibited more than 80% of the isolates. We observed greater levels of antagonism between isolates from adjacent laminae than within. The bacterial isolate library derived from the mat was predominately Gram‐positive, and inhibition within this group was greater than against the few Gram‐negative isolates. Microdiversity of 16S rRNA gene was observed for Bacillus marisflavi isolates, which represented 23 of the 75 isolates in the library. Within this and other groups, the patterns of inhibition and sensitivity varied greatly, suggesting rapid gain and loss of the ability to produce antagonistic secondary metabolites and resistance toward such molecules. Our observations are consistent with the hypothesis that antagonistic interactions are a potential mechanism in addition to physiochemical properties that regulate the vertical distribution of aerobic heterotrophic bacteria in hypersaline microbial mats.